LEARNING THE RULE OF DIPLOMATIC ETIQUETTE IS A BASIC PART OF BEING A DIPLOMAT - Ahmedov Azimjon Ilhomovich; Abdulhakimova Mohlaroyim Baxodirjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: The article explores the role and importance of diplomatic etiquette and also gives some advice and encouragement to young diplomats.Diplomatic etiquette is a manifestation of good behavior in relations between officials, political and public figures representing their country. Etiquettes are defined by the Oxford Dictionary as the customary code of polite behavior in society or among members of a particular profession or group. Diplomats represent themselves with professionalism and respect to foster positive relationships and advance the interests of their nation. This featured article will list does and dont’s for representing your country with diplomatic etiquette abroad.